Eschatologiczna sprawiedliwość Boga wobec historii - Dańczak, Andrzej (Verbum Vitae, 2014)
The course of history, understood in the perspective of faith, requires its evaluation. The issue is associated with the problem of God’s justice, which will demonstrate itself in the parousia. The parousia is the conclusion of history conceived first of all as history of human liberty. At the same time, it means its fulfillment. During the parousia, history does not merely come to an end, but enters the stadium of fullness that is donated by the God of the end of times. Human history becomes the element of eternity and of its transformed time. One of the aspects of parousia is judgment. It demonstrates God’s justice as victorious in regard to all the threads and events of history which were in contradiction to God’s plan towards creation. Purifying justice of God is realized by Christ as a credible co-participant of history. The Lamb “put to death” becomes the sign of measure of the divine love as well as the price of redemption.